Positioning Herb-Infused Cocoa Drinks for Market Success: A Pre-Market Study - Melchor Solimen Lumiked; Cynthia Deponio Garambas; Karl Martin Barnuevo (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2026)
The cacao industry in the Cordillera Administrative Region (CAR) is currently experiencing significant growth, with data indicating a steady increase in cacao production over the past few years. The study aims to introduce innovative approaches to further promote local cacao cultivation and production in the region. One such innovation involves creating cocoa-based drinks infused with locally available herbs, adding value to the cacao produced in the region. Specifically, this study focused on assessing the supply and demand for cacao and cacao-based food products, developing cocoa tablea and cocoa powdered drinks infused with various herbs, and determining the top three most acceptable and preferred formulations. A quantitative descriptive research design was employed for the sensory evaluation, market store checks, and supply and demand analysis. The findings revealed that the supply of cacao in CAR is sufficient to fulfill the requirements of processors producing cacao-based products. Furthermore, it was determined that pandan, guyabano, and turmeric were the most acceptable and preferred herbs for tablea, while thyme, pandan, and guyabano were favored for powdered drinks.